Gambaran Tingkat Risiko Jatuh dan Penanganannya pada Pasien Jiwa di Rumah Sakit - Tiara Sas Dhewanti; Intansari Nurjannah (PSIK FKKMK UGM, 2017)
Background: One of the concerns associated with patient safety is prevention of falls. Patients with mental disorders have a higher risk of falling compared to other patient age, diagnosis of depression, use of antipsychotics medication, and medical therapy management of Electro Convulsive Therapy.Objective: This study was aimed to explore the description of risk for fall levels in the category of psychiatric patients and to identify risk for falls management of mental health patients based on Client Categorization System.Method: A descriptive quantitative research with case study design was performed on 20 psychiatric patients and 4 nurses. The instruments used were Edmonson Fall Risk Assessment Tool (EFRAT) to identify the risk for falls on patients, and Client Categorization System (CCS) to categorize the psychiatric patients. The univariate analysis was used to accomplish the aim of the study.Result: As much as 37,5% patients have risk for falls. The risk of falling level of psychiatric patients occurred mostly on respondents with crisis category (66,7%). No patients with health promotion category have risk for falls. The most activity done with the Nursing Intervention Classification (NIC) (environment modification is using safety equipment. Meanwhile, the most activities done on NIC fall prevention are preparing an appropriate lighting and collaborate with other medical team. Moreover collaboration with other medical team is also needed.Conclusions: Risk for falls on patients with mental health disorders can be found on patients with these category: crisis, acute, and maintenance. Management of patients with mental disorders based in NIC are Fall Prevention and Environmental Modification. ABSTRAKLatar belakang: Pencegahan jatuh merupakan bagian dari keselamatan pasien. Pasien dengan gangguan jiwa mempunyai risiko jatuh lebih tinggi karena usia, diagnosis depresi, penggunaan obat anti psikotik, dan penatalaksanaan terapi medis electro convulsive therapy.Tujuan: Mengetahui gambaran tingkat risiko jatuh dan manajemen penanganannya pada pasien gangguan jiwa beradasarkan Client Categorization System(CCS).Metode: Penelitian ini adalah penelitian deskriptif kuantitatif dengan rancangan case study. Responden terdiri dari 20 pasien gangguan jiwa dan 4 perawat. Instrumen yang digunakan adalah Edmonson Fall Risk Assessment Tool (EFRAT) untuk mengkaji risiko jatuh pada pasien. Sementara, pengkategorian pasien jiwa dilakukan menggunakan instrumen Client Categorization System (CCS). Data hasil penelitian dianalisis menggunakan analisis univariat.Hasil: Hasil penelitian didapatkan sebanyak 37,5% pasien memiliki risiko jatuh. Risiko jatuh pada pasien gangguan jiwa paling banyak terjadi pada responden dengan kategori krisis (66,67%). Pasien dengan kategori health promotion tidak ada yang memiliki risiko jatuh. Aktivitas paling banyak dilakukan pada Nursing Intervention Classification (NIC): Modifikasi lingkungan adalah menggunakan peralatan perlindungan, sedangkan aktivitas pada NIC: Pencegahan jatuh yang selalu dilakukan adalah: identifikasi perpindahan pasien, menyediakan pencahayaan yang cukup dan berkolaborasi dengan anggota tim kesehatan lainKesimpulan: risiko jatuh pada pasien gangguan jiwa dapat terjadi pada pasien dengan kategori krisis, akut, dan maintenance. Manajemen penanganan pada pasien gangguan jiwa berdasarkan NIC adalah pencegahan jatuh dan manajemen lingkungan.